About the comfort of house-buildings with earth walls in San Carlos, Tamaulipas. Issue 1 (31st December 2022) - Chavez-Vega, Fatima; Calvillo-Villicaña, Maria E.; Suarez-Dominguez, Edgardo J.; Arvizu-Sanchez, Eduardo; Estrada-Castro, Karyme E.; Perez-Sanchez, Josue F.; Izquierdo-Kulich, Elena F.
Abstract: Earth construction is a revisited topic due to the low-cost self-production employed in communities and locations where conventional materials (concrete and steel) are not available. One of the properties that are popularly recognized for earth-based buildings is the pleasant indoor thermal sensation. This article presents the development of a model to characterize the temperature of the indoor air applied to adobe houses located in San Carlos, Tamaulipas, Mexico. The model is developed from the heat transfer equations in an ideal case where the temperature is modified by conduction through the wall, and the interior air is heated by convection. In the ideal case, it is considered that there are no doors or windows open because it is what commonly occurs in the earth-based houses during the warmest period of the year. It was found that for a thickness greater than 10 cm there is no significant increase in temperature assuming an outside temperature above 40 °C and an initial indoor temperature of 25 °C. The model characterizes and predict a strong relation between the physical properties of the air and the wall, the thickness of the wall, the dimensions and shape of the room, and the roughness of the outer wall. This consideration makes it possible to quantitatively estimate comfortability based on indoor temperature and wall thickness, which is an expected behavior according to literature. This is important because not only has an impact on the construction of new buildings but also in the critical maintenance of existing houses.